Higher-order differential equations with polynomial solutions associated with classical orthogonal polynomials - Makarov, V.L. (Reports of the National Academy of Sciences of Ukraine, 2020)
A constructive algorithm for constructing differential equations of higher even orders is found, whose solutions are generalized classical orthogonal polynomials. For these polynomials, an explicit image, a three-term recurrence relation, and the appearance of orthogonality conditions with respect to the corresponding distribution function are obtained. The solutions of the corresponding resonance equations are given.